Governança na região transfronteiriça do Iguassu: uma análise sobreo papel do CODETRI - Ferreira, Renann (2024)
Among the fundamental objectives set out in the Constitution of the Federative Republic of Brazil of 1988, the third article includes the reduction of regional inequalities. Moreover, the constitutional paper presents the principles of international relations that govern the country, including the peaceful resolution of conflicts, self-determination, and cooperation between people for the progress of humanity. These principles add up to forming a Latin American community through economic, political, social, and cultural integration. Starting from these constitutional foundations and the foundation of the Democratic Rule of Law, which expresses that all power emanates from the people and can be exercised directly, we intend to answer the following question: how does the Economic, Social and Environmental Development Council of the Trinational Region of Iguaçu - CODETRI is related to the exercise of paradiplomacy in resolving the obstacles in the Iguassu Cross-Border Region? The research aims to investigate if the development councils of the cities of Foz do Iguaçu, Ciudad del Este, Presidente Franco, Puerto Iguazú and the Trinational Development Council will serve as paradiplomatic spaces so that the region formed by their areas of coverage can develop. Specifically, it is intended to outline paradiplomacy within the constitutional principles of international relations; understand the development councils of the four cities; recognize regional obstacles; identify the existence of a possible space for paradiplomacy; verify the viability of CODETRI as a paradiplomatic space for resolving regional obstacles; and analyze the replicability of the model for other frontiers regions. The assumption of the thesis is linked to the existence or not of the paradiplomatic characteristic of the CODETRI based on the logical deduction of the theory. Given the impossibility of controlling the object, which is part of a real context, it was decided to develop the case study through comprehensive theory. The research has an exploratory level, considering that it develops concepts and ideas to get closer to the object that has not yet been explored. The first chapter addresses the fundamental objectives and principles of constitutional international relations relating to work, paradiplomacy and MERCOSUL, covering Working Subgroup nº 18 and the agreements of linked frontiers locations. The following chapter deals with methodological procedures, containing research methods, interviews, data analysis and the state of the art. In the third phase, the four cities and their respective development councils are outlined. The fourth chapter characterizes the Iguassu Cross-Border Region, its obstacles and the formation of the CODETRI. The fifth section presents bibliographical and documentary research and interviews, ending with the analysis of data that revealed the constitution of an incipient paradiplomatic space that seeks the transition to become an interlocutor, through Institutional Cross-Border Paradiplomacy in the Iguassu Cross-Border Region. In addition to finding the academic link with praxis, the research contributes to the development of the region, reinforces the role of the university in the quadruple helix and strengthens the democratic process. Recognizing its limits, the work leaves the possibility of continuing the study due to the need for legal and international institutionalization of the analyzed space.